Posted by **Brock** on Wednesday, August 8, 2012 at 3:31pm.

Write the statements for the basis, the induction hypothesis, and the induction step for the questions below.

1. 1 + 2 +…+n = n(n+1)/2

2. 1/1*2 + 1/2*3+…+1/n*(n+1) = n/n+1

- Calculus -
**Steve**, Wednesday, August 8, 2012 at 3:46pm
for k=1, 1 = 1(2)/2

hyp: as shown

1+...+ k + (k+1) = k(k+1)/2 + (k+1)

= [k(k+1) + 2(k+1)]/2

= (k+1)(k+2)/2

for k=1, 1/1*2 = 1/2

1/1*2 + ... + 1/k(k+1) + 1/(k+1)(k+2)

= k/(k+1) + 1/(k+1)(k+2)

= (k(k+2) + 1)/(k+1)(k+2)

= (k+1)^2 / (k+1)(k+2)

= (k+1)/(k+2)

## Answer This Question

## Related Questions

- Calculus - Use mathematical induction to prove that the statement holds for all ...
- AP Calc - Use mathematical induction to prove that the statement holds for all ...
- Algebra ASAP - so this is a fill in on a worksheet and I am having difficulty as...
- Mathematical induction. I'm stuck. So far I have.. - For all integers n ≥ ...
- computer sciece(Computation Theory) - Find the error in the following proof that...
- Math - Mathematical Induction - 3. Prove by induction that∑_(r=1)^n▒...
- pre-calculus - Prove 3+4+5+...+(n+2) = [n(n+5)]/2 for n>4 Do the first step ...
- precalculus - Can you please check my answers? 1.Find Pk + 1 if Pk=2^K-1/k! ...
- math : induction - The reversal of a string w, denoted w^R, is the string "...
- precalculus - Find Pk + 1 if Pk = 7 + 13 + 19 + ...+[6(k - 1)+1] + (6k + 1) 7 + ...

More Related Questions